Use of acceptable daily intake (ADI) as a health-based benchmark in nutrition research studies that consider the safety of low-calorie sweeteners (LCS): a systematic map - Seneca E. Fitch; Lauren E. Payne; Jennifer L. G. van de Ligt; Candace Doepker; Deepa Handu; Samuel M. Cohen; Njwen Anyangwe; Daniele Wikoff (BMC, 2021)
Abstract Background It is well-recognized that consumers face many challenges in understanding and applying nutritional guidance for low-calorie sweeteners (LCS). Thus, this research aims to (1) assess how benchmarks for safe levels of consumption of LCS are utilized by researchers, and (2) understand how varying use of such benchmarks may contribute to challenges in understanding and applying nutritional guidance for LCS consumption. Methods A systematic mapping exercise was employed to characterize when and how acceptable daily intake (ADI) values are used as health-based benchmarks in nutrition research studies that consider the safety of LCS. Results Based on results from charting 121 studies, our findings demonstrate that comparisons of LCS intake to an ADI derived by an authoritative body have been made in a diverse set of published literature, varying widely in their objectives, approaches, and populations of interest. The majority of studies compared the ADI to intake in a population under study; these represent the type of comparison that is most consistent with the intent of the ADI. Other applications of the ADI included use as a benchmark in experimental studies, risk-benefit analyses, and metabolism studies. Conclusion Although most instances of ADI use were reasonable within the context of the individual studies' objectives, the diversity in use by original-study authors amplifies the continued need for development of "best practices" regarding the use and interpretation of the ADIs in current research. Using comparisons to the ADI can be a helpful way to provide context to research findings. However, in doing so, it is important that researchers utilize the value in a manner specific with its intent, as the ADI is a metric that represents an estimate of the amount of a substance that can be consumed daily over a lifetime without presenting an appreciable risk to health.